Analysis of the Formation of Gairaigo in Website CNN Japan (Morphosemantic Review) - Faniyah, Febri; Masrokhah, Yuni (Ethical Lingua: Journal of Language Teaching and Literature, 2024)
Loanwords in Japanese is gairaigo. Gairaigo is words that come from foreign, except China. The purpose of this research is to get to know about the word formation of gairago in the news website and what kind gairaigo appears the most in the website. The novelty of this research, with previous research is reviewed from morphosemantic. This research used library search techniques to collect data and used descriptive qualitative research techniques. The object of this research is the Japanese news website is called CNN Japan in the period 2023 to 2024. The formation of gairaigo were analyzed using theory by Tsujimura (1996), types of gairaigo were analyzed using theory by Setiawan and the meaning relations were analyzed using theory by Djajasudarma (1993). The results of the research of 51 article that release on website CNN Japan appeared types of gairaigo: Representational, Replacement, Truncated, Altred, and Psuedo Terms. Types that most appears is the Representational type in total 121 from 144 words. Formation gairaigo contained four processes: Affixation, Compounding, Clipping and Borrowing. Meaning relations that most appears is synoym in total 142 words.